El clima organizacional y su relación con la felicidad laboral (2020)
This degree work is focused on the analysis and research on how the organizational climate has a relationship with work happiness and how they influence the development and fulfillment of activities at work, achieving both individual and collective goals and objectives. Subsequently, a respective analysis is shown on how work happiness can vary depending on the work environment and how the activities carried out may have a low performance due to this, in addition the ideal organizational climate that companies must have in order to achieve compliance or even exceed expectations.